A vain attempt: why a change in the reproductive strategy of a rodent population failed to restore ecological balance - Stanislav Myakushko (Theriologia Ukrainica)
Based on long-term observations of a bank vole (Myodes glareolus Schreber, 1780) population, the preconditions, mechanisms, and consequences of changes in reproductive strategy to restore ecological balance are analysed. The studies were conducted in the Kaniv Nature Reserve during different periods of the ecosystem’s existence affected by anthropogenic impact. The characteristics of two cycles of population density dynamics are compared. The first cycle covers the destabilisation stage of the dynamics, which precedes changes in reproductive strategy, whereas the second cycle demonstrates changes in breeding parameters. It was found that in order to compensate the high levels of mortality, reproductive processes intensify. This is achieved by the simultaneous launch of various mechanisms, from increasing individual fecundity to expanding the proportion of individuals involved in reproduction. The first scenario turned out to be unsuccessful and, without adequate ecological support in the form of sufficient feeding resources, caused even higher mortality rates. The size and number of litters dropped to minimum values, and reproduction parameters indicated only a slight success in realising the breeding potential. The most vulnerable was the group of large females, whose fecundity and, consequently, contribution to population growth are the highest. It was found that such processes changed not only the size and weight composition of the population (the proportion of large individuals decreased), but also the sex and age structure (the number of adult females decreased). The decline in the number of large breeding females only exacerbated the misbalance. Population collapse was avoided by expanding the number of females involved in reproduction (extensive reproduction). It is shown that restoration of ecological balance did not follow the change in reproductive strategy. This is supported by the following facts: preservation of signs of a destabilised population dynamics and absence of the previous interdependencies between demographic indices and parameters of feeding resources. As a result, after about a decade of intensive but ineffective reproduction, the population was ‘forced’ to switch to another strategy to restore ecological balance.